Collezioni cartografiche e digital humanities per una nuova fruizione del patrimonio: il caso della Biblioteca Estense Universitaria di Modena - Sara Belotti (Bollettino della Società Geografica Italiana, 2021)
Digital humanities is an emerging discipline that has become increasingly popular in recent years, thanks to the implementation of numerous projects that aim at a dynamic dialogue between digital technologies and humanistic research. This is the scope of the project launched by the Biblioteca Estense Universitaria (BEU) di Modena in 2017, which, in collaboration with the University of Modena and Reggio Emilia, included the study, cataloguing and digitization of the cartographic collection, along with the music collection and the Muratorian collection. This project led to the creation of a digital library, inaugurated in June 2020, which not only allowed the enhancement of the cartographic collection, still little known, and to make it available, albeit only virtually, to scholars, but also led to the adoption of the IIIF protocol that allows to compare, edit, annotate and share the documents of the Este collection and collections that participate in the same circuit, providing new useful tools for research. In this context, the contribution, starting from the presentation of the Estense Digital Library project, presents the cartographic collection of the BEU and offers a reflection on the potential that the new digital media provide for the study of cartography and, more broadly, of heritage in the digital age.